Maternal sociocultural factors linked to childhood iron deficiency anemia at the C.S Pampa Inalámbrica - Paredes Choquehuanca, Angelica María (2025)
Maternal sociocultural factors significantly influence the prevalence of iron deficiency anemia in children in vulnerable contexts. This research aimed to determine the relationship between maternal sociodemographic and cultural factors and the presence of iron deficiency anemia in children aged 6 to 36 months attending the Growth and Development Clinic (CRED) at the Pampa Inalámbrica Health Center in the city of Ilo, Peru. The methodology employed was based on a quantitative, non-experimental, cross-sectional, prospective approach. The sample consisted of 92 mothers. The results highlight a high prevalence of mild anemia (70.7%) in children, with no significant association with maternal marital status or educational level, but with the frequency of consumption of iron-rich foods and the availability of basic services. It is concluded that mild iron deficiency anemia predominated; dietary practices and cultural, social, and economic factors partially influence its prevention in children.